2017
DOI: 10.1371/journal.pntd.0005880
|View full text |Cite
|
Sign up to set email alerts
|

Neurosyphilis in Africa: A systematic review

Abstract: IntroductionNeurological involvement is one of the most important clinical manifestations of syphilis and neurological disease occurs in both early and late syphilis. The impact of HIV co-infection on clinical neurosyphilis remains unclear. The highest prevalence of both syphilis and HIV is in Africa. Therefore it might be expected that neurosyphilis would be an important and not uncommon manifestation of syphilis in Africa and frequently occur in association with HIV co-infection; yet few data are available o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 43 publications
4
14
1
Order By: Relevance
“…This low prevalence may be due either to ART use in most patients, or possibly having been previously treated with antibiotics, for a different indication, that have activity against Treponema pallidum. Our findings on neurosyphilis fit with a systemic review of neurosyphilis in Africa by Mark et al (52), which found only two patients with meningitis (3.3%).Another study done in Brazil by Jacquelline et al had showed to be 1% among HIV positive patient with neurologic features (53). In contrast, a study by Borden et al showed that 23.5% seropositive for T.pallidum patients who were not on ART had neurosyphilis.…”
Section: Discussionsupporting
confidence: 88%
“…This low prevalence may be due either to ART use in most patients, or possibly having been previously treated with antibiotics, for a different indication, that have activity against Treponema pallidum. Our findings on neurosyphilis fit with a systemic review of neurosyphilis in Africa by Mark et al (52), which found only two patients with meningitis (3.3%).Another study done in Brazil by Jacquelline et al had showed to be 1% among HIV positive patient with neurologic features (53). In contrast, a study by Borden et al showed that 23.5% seropositive for T.pallidum patients who were not on ART had neurosyphilis.…”
Section: Discussionsupporting
confidence: 88%
“…This low prevalence may be due either to ART use in most patients, or possibly to having been previously treated with antibiotics, for a different indication, that have activity against Treponema pallidum. Our findings on neurosyphilis fit with a systemic review of neurosyphilis in Africa (22), which found only two patients with meningitis (3.3%).Another study done in Brazil had shown the prevalence of neurosyphilis to be 1% among HIV positive patients with neurologic features (23). In contrast, a study by Alverez et al showed that 23.5%…”
Section: Discussionsupporting
confidence: 87%
“…Traditionally, the neurological complications of infectious diseases (HIV infection, tuberculosis and malaria) have been considered to account for a significant portion of the neurological diseases found in the countries of Sub Saharan Africa. [17][18][19] Contrary to this belief, cerebrovascular disease accounted for 51.0% of neurological admissions in this urban sample, 55.3% of the neurological mortality and 79.7% of the neurological disability among the survivors. Other studies in Sub-Saharan Africa have reported crude yearly stroke incidence rates of 94.5-107.9/100,000, associated with high mortality rates.…”
Section: Discussioncontrasting
confidence: 81%